The Well-Being of Play in Academia - Bill Michael Linde (University of Huddersfield Press, 2021)
This article examines the well from which learning, teaching, and research originate. It investigates how to perform these three aspects of academic practice well and to do it in a playful manner. Instead of repeating existing knowledge and scientific methods punctiliously, the playful academic experiences and presents knowledge in new or alternative ways. Playfulness more often results in discoveries and inventions that are otherwise unthinkable.Through an analysis of a selection of Plato's myths, allegories, and imagery, the article demonstrates how very complicated subject matters can be illustrated in a playful, synecdochic form, hereby making the unfathomable easier to approach and understand.Examining Plato's concept of 'agalma' - the beautiful ornament of wisdom - the article discusses how we can see academia as a jewellery box, or as a plaything. Agalma allows us to see learning, teaching, and research as an adventurous journey or as a playful labyrinth leading into all dimensions of being.